The Industrial policy process in Ghana - Zakari, Abubakari (UNIDO ViennaAT, 2013)
Presents Ghana's industrial policy context which covers the background, economic structure and policy interventions in the country; describes the industrial policymaking process; discusses the outputs and examines the coordination mechanisim of the process; and discusses the lessons learnt.